The Impacts of Maoist Conflict in Nepal - Guragain, Govinda (TUTA Journal, 2022)
Conflict is a burning issue in the contemporary world. It creates major threat to world peace. The issues which are closely related to the social and economic condition of any country such as caste, ethnicity, gender, class, religion, poverty, hunger etc. are the precursor of the conflict. Conflict is the main cause of violence, fight, battle, war or even insurgencies and the terrorism. Human being and the society are greatly affected by conflict and they live under mental tension and terror. The development, peace and prosperity depends the peaceful condition of the society. In context of Nepal there are different variables of conflict overlapping on each other such as castes, religion, ethnicity, gender, language, region etc. As Nepal is declared Federal Republic by Interim Constitution of Nepal 2063 and Nepal is in the process of restructuring the states. These are major hurdles on the path of development. It is very important to address these differences properly otherwise there may raise the violent conflict again in the future. In the post conflict era of Nepal brought a lot of positive changes which brought remarkable impacts in the life of Nepalese people.